Penerapan Metode Penemuan Terbimbing dalam Peningkatan Pemahaman Konsep Diagram Batang di Kelas IV SDN Karangtengah 1 Kota Blitar - Endang Puji Astuti (Civiliza Publishing, 2021)
Abstract. Mathematics education in elementary school is the beginning of a child's beginning to explore his ability to understand concepts in mathematics and the knowledge gained will greatly influence him at the next level of education. In learning to make a bar chart in Class IV Semester 2 of SDN Karangtengah 1, Sanawetan District, Blitar City, in the 2020/2021 academic year, it can be seen that there are still many students who do not understand the concept. This is due to the frequent online learning during the corona pandemic, so teachers have not yet completed learning. Such conditions require teachers to conduct research. The research used is a qualitative research on learning Mathematics with the type of Classroom Action Research (CAR). Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The method used to solve problems in learning to make Bar Charts is the Guided Discovery method, which is a technique or method used by the teacher to teach in front of the class, where the teacher divides the task of researching a problem into the class.